Structural and electrical properties of AlN thin films on GaN substrates grown by plasma enhanced-Atomic Layer Deposition. (July 2019) - Schilirò, Emanuela; Giannazzo, Filippo; Bongiorno, Corrado; Di Franco, Salvatore; Greco, Giuseppe; Roccaforte, Fabrizio; Prystawko, Pawel; Kruszewski, Piotr; Leszczyński, Mike; Krysko, Marcin; Michon, Adrien; Cordier, Yvon; et al.
Abstract: Aluminum nitride (AlN) thin films have been deposited by Plasma Enhanced Atomic Layer Deposition (PE-ALD) onto GaN-Sapphire substrates. The morphological, structural and electrical properties of AlN films with different thickness (from 5 to 15 nm) have been investigated. They uniformly cover the underlying GaN substrate without pinholes and cracks. All the AlN thin films show c-axis orientation and their in-plane crystalline arrangement perfectly matches the hexagonal structure of GaN substrate. In particular, the cross-sectional TEM analysis demonstrated that the first AlN layers are well aligned with respect to the GaN (0001) substrate, while stacking faults formation is observed in the upper part of the films. Finally, electrical measurements by Hg-probe on as-deposited AlN showed very low current leakage across these layers and the presence of a high density two-dimensional electron gas (>2 × 10 13 cm −2 ) at the AlN/GaN interface.